Integrasi Analisis Reliability Dan Availability Dalam Penentuan Interval Perawatan Optimal Excavator - Faisal Rahman; Firda Herlina; Ice Trianiza; Saifullah Arief (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
Effective maintenance is an essential factor in ensuring the reliability and availability of equipment, especially for heavy equipment that operates intensively. This study aims to optimize the maintenance interval of excavator units by considering the value of reliability against time, to obtain a balance between reducing the risk of failure and maximizing operational availability. Historical data of time between failures (TBF) and time to repair (TTR) were collected from a PC 200 excavator unit operating in a coal mine in South Kalimantan from January 2024 to June 2025. Initial analysis was carried out using a Pareto diagram to identify critical systems, followed by failure mode and effect analysis (FMEA) to determine repair priorities. TBF and TTR modeling were tested with four probability distributions (Normal, Lognormal, Weibull, and Exponential) using the Anderson–Darling goodness-of-fit test, with the result that both data follow a Lognormal distribution. Distribution parameters were used to calculate mean time between failures (MTBF), mean time to repair (MTTR), the reliability function R(t), and availability. The results show an increase in availability from 96.15% to 96.59% after implementing the selected distribution, as well as a decrease in MTTR from 11.21 hours to 9.92 hours. Analysis of the relationship between reliability and availability resulted in an optimal maintenance interval in the range of 230–245 hours, when reliability remains above 90% and availability is around 96%.